Manufacturing and Examination of Vaginal Drug Delivery System by FDM 3D Printing - Petra Arany; Ildikó Papp; Marianna Zichar; Géza Regdon; Mónika Béres; Melinda Szalóki; Renátó Kovács; Pálma Fehér; Zoltán Ujhelyi; Miklós Vecsernyés; Ildikó Bácskay (MDPI AG, 2021)
Vaginal drug delivery systems can provide a long-term and constant liberation of the active pharmaceutical ingredient even for months. For our experiment, FDM 3D printing was used to manufacture the vaginal ring samples from thermoplastic polyurethane filament, which enables fast manufacturing of complex, personalized medications. 3D printing can be an excellent alternative instead of industrial manufacturing, which is complicated and time-consuming. In our work, the 3D printed vaginal rings were filled manually with jellified metronidazole or chloramphenicol for the treatment of bacterial vaginosis. The need for manual filling was certified by the thermogravimetric and heatflow assay results. The manufactured samples were analyzed by an Erweka USP type II Dissolution Apparatus, and the dissolution profile can be distinguished based on the applied jellifying agents and the API's. All samples were considered non-similar based on the pairwise comparison. The biocompatibility properties were determined by prolonged MTT assay on HeLa cells, and the polymer could be considered non-toxic. Based on the microbiological assay on E. coli metronidazole and chitosan containing samples had bactericidal effects while just metronidazole or just chitosan containing samples bacteriostatic effect. None of these samples showed a fungistatic or fungicide effect against C. albicans. Based on our results, we successfully manufactured 3D printed vaginal rings filled with jellified metronidazole.